Nurses' knowledge on pressure ulcer prevention: An updated systematic review and meta-analysis based on the Pressure Ulcer Knowledge Assessment Tool - Wu, Jing; Wang, Bangjun; Zhu, Liping; Jia, Xiaoli (Frontiers in Public Health, 2022)
Background: Pressure ulcers (PUs) are an indicator of the quality of nursing care and nurses can prevent PYUs well if they have sufficient knowledge. Different studies in this field have reported different results. The aim of this study was to estimate the pooled score of nurses' knowledge about PU prevention based on the Pressure Ulcer Knowledge Assessment Tool (PUKAT). Methods: In this systematic review and meta-analysis, databases including Web of Science, ScienceDirect, PubMed, and Scopus were searched. All studies published in English that reported the status of nurses' knowledge of PU prevention based on PUKAT were included in the analysis. Based on heterogeneity between the studies, the data were analyzed using a random-effects model. Results: The scores of PU prevention knowledge in nurses and nursing students were (51.5%; 95% CI: 45.8%-57.2%) and (48.9%; 95% CI: 42.5%-55.2%), respectively. As the age of the participants increased, the score of pressure ulcer prevention knowledge increased significantly (p=0.028). The publication bias was not significant. The highest and lowest knowledge scores in nurses and nursing students were related to the fourth dimension (nutrition) and the fifth dimension (preventive measures to reduce the amount of pressure/shear), respectively. Conclusion: Knowledge of nurses and nursing students about PU prevention is insufficient. Providing regular training to nurses and including the principles of PU prevention in the curriculum of nursing students to improve their knowledge seems necessary.